The modern trends in surgery of extensive tumors affecting the front and mean cranial fosses in nasal cavity and paranasal sinus - S. Ya. Chebotaryov (Бюллетень сибирской медицины, 2008)
2—3% of head and neck tumors are comprised by nasal and paranasal sinus’ masses. Complex method based on surgcical operation with maximal cytoreduction is the mainstay of treatment. Pecularities of surgical planning and technique in treatment of paranasal sinus tumors invading the skull base are considered in the article. Short- and long-term surgical results have been analyzed. Long-term results first of all depend on radicality of operation, histological structure of the tumor and its sensitivity to ajunctive methods of treatment. These used techniques are the only possible in this kind of mass lesions.